Coastal Blur: a fish market and community forum conceptualised on the netting of liminal negotiation in Kalk Bay Harbour - Steenberg, Elandré (University of the Free State, 2022)
The following research investigates how the liminal negotiation of space can spatially net the phenomenon of thresholds, time and transition space between land and sea at the coast of Kalk Bay. Coastal communities such as Kalk Bay have much more to offer than quaint shops and pretty boats. These communities subconsciously act as nets that negotiate the liminal conversations between land and sea. Over the years, small-scale fisheries have suffered a great deal with the modernisation of fishing technology which inevitably caused the deterioration and fragmentation of small-scale fishing community culture. In order to preserve this coastal culture, an architectural intervention can be conceptualised on the premise of encouraging economic, social, and ecological development and activity. The thesis presents research on how to adopt critical regionalism in architecture in a way that celebrates and sensitively 'nets' a place for gathering for Kalk Bay's fishing community and visitors. The research question for the study is as follows: How can the act of liminal negotiation conceptualize a fish market and community forum which mitigates the transitional space between land and sea in order to reconcile the social fabric of Kalk Bay with the commercial edges of the harbour? The theoretical premise of place and time assists in revealing how Kalk Bay finds itself embodying what Edward Relph coins as 'placelessness' in its fragmented state (Najafi & Shariff, 2011: online). The loss of identity could be counteracted by spatially acknowledging the palimpsest of thresholds that resembled the deterioration and fragmentation the site had endured This helped defamiliarise local culture and environmental aspects to reveal new understandings of old ways of life. These approaches of spatial netting are implemented to achieve a contextual, cultural, and regional-specific design that aims to blur the liminal between land and sea.
Dissertation(M.Arch. (Architecture))--University of the Free State, 2022
Keywords: Placelessness; Thresholds; Liminal; Time; Kalk Bay